Common Bark Beetle Pests of Florida - Sawyer Adams; Jiri Hulcr (EDIS)
This new 4-page guide was created specifically as an aid for youth forestry knowledge competitions, including 4-H and Future Farmers of America. Along with a collection of the listed beetles, it is suitable as a beginner’s introduction to the most important pine pests in Florida. Written by Sawyer Adams and Jiri Hulcr and published by the UF/IFAS 4-H Youth Development Program.